2022
DOI: 10.1089/can.2022.0011
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol Impairs Brain Mitochondrial Metabolism and Neuronal Integrity

Abstract: Background: The mechanisms underlying the clinical effects of CBD remain poorly understood. Given the increasing evidence for CBD's effects on mitochondria, we sought to examine in more detail whether CBD impacts mitochondrial function and neuronal integrity. Methods: We utilized BE(2)-M17 neuroblastoma cells or acutely isolated brain mitochondria from rodents using a Seahorse extracellular flux analyzer and a fluorescent spectrofluorophotometer assay. Mitochondrial ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 54 publications
3
11
0
Order By: Relevance
“…Notably, at the lower NPCBD dose (0.01 mg/mL, corresponding to 0.20 μM of CBD), OCR values affected by the OGD insult were restored, closely resembling those of the untreated (HEALTHY) cells. These findings align with previous studies using CBD at similar doses in cell lines such as hippocampal neurons (HT22 cells) and BE(2)-M17 neuroblastoma cells …”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Notably, at the lower NPCBD dose (0.01 mg/mL, corresponding to 0.20 μM of CBD), OCR values affected by the OGD insult were restored, closely resembling those of the untreated (HEALTHY) cells. These findings align with previous studies using CBD at similar doses in cell lines such as hippocampal neurons (HT22 cells) and BE(2)-M17 neuroblastoma cells …”
Section: Resultssupporting
confidence: 92%
“…Similar results have been reported in other studies employing monocultures and cocultures . Overall, results from Seahorse analysis indicate a neuroprotective effect provided by NPCBD, reducing OGD-induced oxidative stress, in line with previous findings. , …”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Direct actions of cannabinoids on respiratory complexes have been described [ 35 ] independently of their action on mitochondrial cannabinoid receptors [ 22 ]. In particular, several studies have reported specific actions of THC and CBD on mitochondrial respiratory chain activity, ROS production and cellular integrity, promoting toxicological effects in certain cells that may be potentially relevant for clinical populations [ 36 ]. Furthermore, an increasing number of experimental evidences link cannabinoid modulation of mitochondrial metabolism to specific physiological processes, such as cognition and memory [ 19 ], underlining the need for accurate characterization of extracts to obtain the strains of greatest therapeutic interest.…”
Section: Discussionmentioning
confidence: 99%